2019
DOI: 10.1101/648071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular organization of soluble type III secretion system sorting platform complexes

Abstract: 40Many medically relevant Gram-negative bacteria use the type III secretion system (T3SS) to 41 translocate effector proteins into the host for their invasion and intracellular survival. A multi-42 protein complex located at the cytosolic interface of the T3SS is proposed to act as a sorting 43 platform by selecting and targeting substrates for secretion through the system. However, the 44 precise stoichiometry and 3D organization of the sorting platform components is unknown. Here 45 we reconstitute soluble c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The D ~ 1.1 µm 2 /s diffusive state is consistent with our previous result obtained with PAmCherry-YeSctL, based on which we concluded that both eYFP-YeSctQ and eYFP-YeSctL diffuse at the same slow rate as part of the same complex 19 . The SctLQ interaction is also supported by a number of previous studies 18,20,21 . On the other hand, the D ~ 2.9 µm 2 /s eYFP-YeSctL diffusive state has not been previously observed.…”
Section: Yesctl Shares One Diffusive State With Yesctqsupporting
confidence: 76%
See 2 more Smart Citations
“…The D ~ 1.1 µm 2 /s diffusive state is consistent with our previous result obtained with PAmCherry-YeSctL, based on which we concluded that both eYFP-YeSctQ and eYFP-YeSctL diffuse at the same slow rate as part of the same complex 19 . The SctLQ interaction is also supported by a number of previous studies 18,20,21 . On the other hand, the D ~ 2.9 µm 2 /s eYFP-YeSctL diffusive state has not been previously observed.…”
Section: Yesctl Shares One Diffusive State With Yesctqsupporting
confidence: 76%
“…Importantly however, a SaSctL2:SaSctN heterotrimer was consistently observed in any complex that included these two proteins 20 . Dynamic light scattering was used to determine the relative size of cytosolic injectisome proteins and their respective complexes 21 .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, we show that InvCΔ79 can form dimer sets in solution in the absence of its N‐terminal domain (Figure ), suggesting that additional domains contribute to the oligomerization state. The N‐terminal domain of orthologue T3SS ATPases can also bind to a negative regulator (OrgB in Salmonella ) and display affinity for lipids . In our hands, the N‐terminal domain of the full length InvC suffered rapid proteolysis during and after purification (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…The T3SS ATPases fold in three domains. The N‐terminal domain is considered to be important for stable assembly of higher oligomers; it binds to the ATPase negative regulator (OrgB in Salmonella ) and presents lipid affinity . The predicted ATPase core is the central and most conserved domain.…”
Section: Introductionmentioning
confidence: 99%